Analisis Yuridis Terhadap Alih Fungsi Lahan Pertanian Ke Non-Pertanian dalam Perspektif Perlindungan Lahan Pangan Berkelanjutan - Ryan Sindhu Pratama (Al-Wasathiyah: Journal of Islamic Studies, 2026)
The conversion of agricultural land into non-agricultural land in Indonesia has increased significantly over the past five years, affecting food security, the environment, and socio-economic sustainability. This study aims to analyze the juridical aspects of such land conversion, evaluate the effectiveness of national and regional regulations, and review Supreme Court decisions related to disputes over the conversion of agricultural land. The research method employs a normative juridical approach through literature study, analysis of current legislation including Law No. 11 of 2020 on Job Creation, the Basic Agrarian Law, and relevant ministerial regulations, as well as recent court decisions. The results show that although regulations exist to protect sustainable food agricultural land, there are still legal gaps that allow uncontrolled land conversion. Law enforcement and supervision of regulatory implementation remain weak, therefore stronger policy integration and stricter enforcement of legal sanctions are required. This study provides recommendations to strengthen the protection of sustainable food agricultural land through technology-based monitoring, harmonization of national and regional regulations, and public education on the importance of preserving agricultural land.